Pharmacist-led antimicrobial stewardship at transitions of care from inpatient hospital to home: a scoping review - Mishka Danchuk-Lauzon (Cambridge University Press, 2024)
Abstract Objective: To summarize available literature and highlight research gaps pertaining to the role of a pharmacist in providing antimicrobial stewardship (AMS) interventions for antibiotics at transitions of care (TOC) from inpatient hospital settings to home. Design: Scoping review. Methods: This scoping review follows the Arksey and O'Malley methodological framework. The literature search was conducted using the MEDLINE (OVID) database. Results: The MEDLINE (OVID) search returned 45 results. Of these, 26 were excluded during title and abstract screening and 11 were excluded after full-text review. Overall, eight studies were included in this scoping review. In six of the studies, AMS interventions were pharmacist-led. In two studies, they were led by an AMS team which included a pharmacist. Six of the studies used a similar intervention where a pharmacist led the review of antibiotics prior to patient discharge and made recommendations to change therapy where appropriate. The details of how these interventions were carried out vary between studies. Conclusions: Overall, all studies included in this scoping review concluded that pharmacists have a role in providing AMS interventions at TOC. This scoping review summarized available literature pertaining to the role of the pharmacist in providing AMS interventions for antibiotics at TOC. Research gaps that were highlighted are optimal level of AMS training for pharmacists providing AMS interventions, optimal workflow, ideal method of communication to the prescriber, and quality improvement metrics.